Dimensi Humanisme Teosentris Pendidikan Islam: Tinjauan Mazhab Filsafat Pendidikan Islam Peripatetik, Iluminasi, dan Sufi - Dwi Fitri Wiyono (VICRATINA, 2018)
Abstract The dialectic of the philosophy of Islamic education in the thinking of the three main schools of philosophy, throughout its history is always interesting to discuss. The theocentric-style dimension of humanism is characteristic of the philosophy of Islamic education. The view of humanism in western modern philosophy is interpreted as limited as human-centered anthropocentric freedom, while humanism in Islamic philosophy is characterized by theocentric humanism. three Islamic thinkers: covering three important schools, namely: Peripetik (masy-syaiya) by Ibn Sina, Illumination (Isyraqiyah) by Suhrawardi, Irfan (Genosis, ma’rifat) by Ibn Arabi. The three schools have the same substance value of humanism, especially in the analysis of the context of Islamic education, namely, the soul of the soul relies on the theocentric theology of humanism even though the approaches of each of the Islamic philosophers are different from each other. Keywords: dimension, theocentric humanism, the philosophy school of Islamic education